The Efficacy and Safety of Vonoprazan and Amoxicillin Dual Therapy for Helicobacter pylori Infection: A Systematic Review and Network Meta-Analysis - Ligang Liu; Fang Li; Hekai Shi; Milap C. Nahata (MDPI AG, 2023)
The eradication of Helicobacter pylori (H. pylori) infection remains challenging due to increasing bacterial resistance. Resistance rates to clarithromycin, metronidazole, and levofloxacin were higher than 30% in the USA, making current therapies less effective. Vonoprazan triple therapy (VAC) has demonstrated similar efficacy and safety profiles compared to PPI-based triple therapy (PPI). However, the eradication rate of vonoprazan dual therapy (VA) for H. pylori infection in comparison to VAC, and PPI was poorly established. Electronic databases were searched up to 6 October 2022, to identify studies examining the safety and efficacy of VA compared to VAC and PPI. Six studies were included. For empiric therapies among treatment naïve patients, VA, VAC, and PPI did not achieve high cure rates (>90%). The comparative efficacy ranking showed VAC was the most effective therapy, followed by VA, and PPI. The results were similar for clarithromycin-resistant infections. The comparative safety ranking showed VA ranked first, whereas PPI triple therapy was the least safe regimen. These findings should guide the selection of the most effective and safe treatment and conduct additional studies to determine the place of vonoprazan dual versus triple therapies in patients with H. pylori from various countries across the world.